(untitled) (LEARNing Landscapes, 2012)
A group of teachers working with children, parents, and friends of the school have explored ways to develop environmental, artistic, social, and cultural awareness through events and workshops based on museum education. They saw power in the notion of collections of things that would impact on children’s formal and informal learning. This article describes aspects of museum education in school.